A Lagrangian relaxation approach to a coupled lot-sizing and cutting stock problem - Gramani, M. C. N.; Franca, P. M. [UNESP]; Arenales, M. N. (Elsevier B.V., 2009)
Industrial production processes involving both lot-sizing and cutting stock problems are common in many industrial settings. However, they are usually treated in a separate way, which could lead to costly production plans. In this paper, a coupled mathematical model is formulated and a heuristic method based on Lagrangian relaxation is proposed. Computational results prove its effectiveness. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Lot-sizing; Cutting stock; Production planning; Mixed-integer programming; Lagrangian relaxation